Influence of polystyrenesulfonate on electron transfer quenching of ruthenium trisbipyridine luminescence by viologens: Non-covalent assembly and covalent tethering of the ruthenium complex - KELLY, JOHN MOFFAT (My University, 2012)
A new copolymer (RuB-PSS) of ruthenium(ii)bis-(2,2?-bipyridine)(4- vinyl 2,2?-bipyridine) and styrene sulfonate was prepared which tethers the ruthenium chromophore directly to the polymer backbone. The photophysical properties of the copolymer, and its luminescence quenching by viologens, were compared with those of ruthenium(ii)tris-bipyridine, [Ru(bpy) 3] 2+, bound non-covalently to polystyrenesulfonate (PSS) via hydrophobic and electrostatic interactions. Enhancement of ruthenium polypyridyl complex luminescence in both systems is due to decreased rates of non-radiative decay when removed from bulk water as well as reduced oxygen quenching. Molecular dynamics simulations show an open PSS chain conformation with induction of local curvature around the ruthenium centres. Hence, the complexes remain exposed to water, albeit less so than in bulk solution, as evidenced by low enhancement of bound [Ru(phen) 2dppz] 2+ emission. Quenching by O 2 is hindered for both systems due to combined polarity, ionic strength, and viscosimetric effects that influence local concentrations and diffusion of reactants. Electron transfer quenching of the Ru centre by zwitterionic propyl viologen sulfonate (PVS 0) and cationic methyl viologen (MV 2+) is enhanced for [Ru(bpy) 3] 2+/PSS, but retarded for RuB-PSS, despite the attraction of the quenchers for PSS. PSS binding hinders separation of the electron transfer products relative to aqueous solution, excepting an increase for RuB-PSS/PVS 0. We conclude that anionic hydrophobic polymers such as PSS can differentially influence forward- and reverse- electron transfer reactions depending on the charge and hydrophobicity of the reactants. In the context of small molecule binding, we find that PSS provides a tenable model for DNA
PUBLISHED
Keywords: new copolymer (RuB-PSS); new copolymer (RuB-PSS)